Aspirasi Keluarga Nelayan Pantai Utara Jawa Terhadap Pendidikan Anak - Inayah Hidayati; Mochammad Wahyu Ghani; Intan Adhi Perdana Putri; Widayatun Widayatun; Augustina Situmorang (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2021)
So far, fishermen are associated with the poor with low education. This is due to the livelihood of fishermen who depend on the sea, which is very dynamic and uncertain. However, during the last 20 years, there has been a change in the perspective and aspirations of fishermen’s families towards their children’s education. The factors of fishermen’s livelihood, which are increasingly difficult and increasing accessibility, are expected to change the perspective on education. This research aims to explore the factors that change the aspirations of fishermen’s families towards education, both formal and informal education in Purworejo Village - Demak. The qualitative research method with ten informants conducted in-depth interviews, three focused discussions, and field observations to understand the existing phenomena. Focused discussions were conducted online and offline due to the COVID-19 pandemic situation in the research area. Data collection was carried out in July-August 2020 and March 2021. The results showed that the fishermen had seen the importance of their children getting a higher education. The increasing aspirations of fishermen’s parents towards education cannot be separated from the Family Hope Program (Program Keluarga Harapan or PKH), which can at least increase the school participation level of fishermen’s children. Parents expect their children to have a wider choice of jobs than those who live by profession as a fisherman, namely employee of the last resort.